Evidence-based Potential Therapeutic Applications of Cannabinoids in Wound Management. (18th August 2022) - Kibret, Berhanu Geresu; Patel, Sheel; Niezgoda, Jonathan; Guns, William; Niezgoda, Jeffrey; Gopalakrishnan, Sandeep; Baban, Babak; Cubillos, Paola; Villeneuve, David; Kumar, Pritesh
ABSTRACT: BACKGROUND: Although wound management is a major component of all domains of healthcare, conventional therapeutics have numerous limitations. The endocannabinoid system of the skin, one of the major endogenous systems, has recently been connected to wound healing. Cannabinoids and their interactions with the endogenous chemical signaling system may be a promising therapeutic option because they address some of the fundamental pathways for physiologic derangement that underpin chronic integumentary wounds. RECENT ADVANCES: The therapeutic applications of cannabinoids are increasing because of their legalization and resulting market expansion. Recently, their immunosuppressive and anti-inflammatory properties have been explored for the treatment of wounds that are not effectively managed by conventional medicines. CRITICAL ISSUES: Failure to manage wounds effectively is associated with reduced quality of life, disability, mortality, and increased healthcare expenditures. Therapeutic options that can manage wounds effectively and efficiently are needed. In this review, the authors summarize recent advances on the use of cannabinoids to treat skin disorders with an emphasis on wound management. FUTURE DIRECTIONS: Effective wound management requires medicines with good therapeutic outcomes and minimal adverse effects. Despite the promising results of cannabinoids in wound management, further controlled clinical studies are required to establish the definitive role of these compounds in the pathophysiology of wounds and their usefulness in the clinical setting.